1999
DOI: 10.1182/blood.v93.7.2186
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Prothrombotic Polymorphisms and Atherogenic Factors on the Risk of Myocardial Infarction in Young Males

Abstract: Several recent studies evaluated a possible effect of the prothrombotic polymorphisms such as 5,10 methylenetetrahydrofolate reductase (MTHFR) nt 677C → T, factor V (F V) nt 1691G → A (F V Leiden), and factor II (F II) nt 20210 G → A on the risk of myocardial infarction. In the present study, we analyzed the effect of these prothrombotic polymorphisms, as well as apolipoprotein (Apo) E4, smoking, hypertension, diabetes mellitus, and hypercholesterolemia, on the risk of myocardial infarction in young males. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…There was one prospective study 6 and 33 cross-sectional case–control studies. Twenty-two studies included Caucasian patients 4 , 6 , 11 , 13 , 14 , 16 , 18 , 20 , 21 , 23 27 , 29 , 33 39 , 9 included non-Caucasians 8 , 10 , 12 , 15 , 17 , 19 , 28 , 30 , 32 , and 3 did not depict ethnicity of subjects 5 , 22 , 31 . As the study population overlapped in two reports 6 , 39 , Maren’s data 39 were evaluated only in the >55-year-old subgroup analysis and not in the overall analysis.…”
Section: Resultsmentioning
confidence: 99%
“…There was one prospective study 6 and 33 cross-sectional case–control studies. Twenty-two studies included Caucasian patients 4 , 6 , 11 , 13 , 14 , 16 , 18 , 20 , 21 , 23 27 , 29 , 33 39 , 9 included non-Caucasians 8 , 10 , 12 , 15 , 17 , 19 , 28 , 30 , 32 , and 3 did not depict ethnicity of subjects 5 , 22 , 31 . As the study population overlapped in two reports 6 , 39 , Maren’s data 39 were evaluated only in the >55-year-old subgroup analysis and not in the overall analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies in which traditional risk factors were excluded, the MTHFR homozygous mutant genotype (V/V) conferred a higher risk. 39,41 The MTHFR genotype has been shown to interact with other risk factors for cardiovascular disease, such as Factor V Leiden, 25,26 apo E variants, 48 and diabetes, 49 to increase risk.…”
Section: Genetic Modulation Of Homocysteine and Risk For Cardiovasculmentioning
confidence: 99%
“… 11 A synergistic effect between atherogenic risk factors and thrombogenic mutations in the pathogenesis of MI has also been suggested. 6 In particular, the concomitant presence of smoking and factor V Leiden mutation was found to increase the risk of MI in young men. 12 , 13 Therefore, in our patient, MI may have been a consequence of the synergism between inherited thrombophilia and cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the association between the homozygous 677TT MTHFR polymorphism and MI have been examined, but the results of studies demonstrated that the role of MTHFR in MI was not well established. 6 Moreover, other studies have failed to establish a definitive role of certain inherited thrombophilias in MI. 7 Recently, however, large-scale multigenic association studies have revealed that the C677T MTHFR polymorphism is a significant risk factor associated with the prevalence of MI.…”
Section: Discussionmentioning
confidence: 99%